A multi-sensor system and its error compensation for on-machine measurement. Issue 1 (January 2020) - Zhang, Zhenjiu; Ren, Mingjun; Liu, Mingjun; Xia, Linzhong; Sun, Lijian
Abstract: In order to enhance the accuracy and efficiency of the measurement of on-machine test, a multi-sensor system is developed in this paper. This multi-sensor system consists of a touch trigger probe and a laser displacement sensor, so this measurement system has both the characteristics of high efficiency of laser displacement sensor and high precision of trigger probe. To enhance the accuracy of this measurement system, the main errors including sensor errors and motion errors of machine tools are tested and compensated respectively. Finally, experiments are conducted to validate that this multi-sensor system is suitable for on-machine measurement of workpiece.